The Effect of Life Expectancy, Open Unemployment Rate, and Government Spending in The Education Sector on The Human Development Index in North Sumatra Province, Indonesia - Muhammad Alhasymi Matondang Hasymi; Muhammad Abdi; Fahmi Apriyansyah Siregar; Runggu Sihombing; Jonathan Brando Saragi; Nadia Enjel Lina Silalahi (Outline Journal of Economic Studies, 2025)
This study aims to analyze the effect of Life Expectancy Rate (AHH), Open Unemployment Rate (TPT), and Government Expenditure in the Education sector on Human Development Index (HDI) in North Sumatra Province in the period 2010-2024. This research uses a quantitative approach with a literature study method. The data used is secondary time series data obtained from the publication of Badan Pusat Statistik (BPS). The analysis technique used is multiple linear regression with the help of E-Views 10 software. Tests were carried out through the classical assumption test, the coefficient of determination test, the simultaneous F test, and the partial t test. The results showed that simultaneously the three independent variables had a significant effect on HDI. Partially, AHH and government spending in the education sector have a positive and significant effect on HDI, while TPT has a negative and significant effect. The Adjusted R-squared value of 0.985 indicates that the model is able to explain 98.5% of the variation in HDI. This finding confirms that improving the quality of health, reducing unemployment, and investing in the education sector are important factors in supporting sustainable human development in North Sumatra Province.